Attention-Deficit/Hyperactivity Disorder with Inadequate Response to Stimulants: Approaches to Management - Childress, Ann C.; Sallee, Floyd R. (CNS drugs, 2014)
Attention-deficit/hyperactivity disorder, or ADHD, is the most frequently occurring neurobiological disorder in childhood and is defined by symptoms of inattention and/or hyperactivity and impulsivity that are excessive when compared with other individuals at the same developmental level. ADHD can be successfully treated pharmacologically and stimulant medications are considered a first-line treatment. However, 20–35 % of subjects in clinical trials may have an inadequate response to initial stimulant treatment. There is no standard definition of inadequate response. In many clinical trials, response is defined as a percentage improvement on the Attention-Deficit/Hyperactivity Disorder Rating Scale alone, while in others the change in Clinical Global Impression-Improvement score has also been employed. Other outcome measures have also been used. A more meaningful definition for inadequate response is one that does not produce sufficient reduction of symptoms to produce functional improvement. The literature reveals many factors that may contribute to inadequate response to treatment. Among these are poor adherence, severity and/or complexity of ADHD, inadequate stimulant dosing and/or dose-limiting adverse effects. The reasons for poor adherence should be determined. Common factors include adverse effects, lack of effectiveness, concerns about addictive potential, difficulty ingesting the medication and cost. For patients with inadequate dosing, medication optimization should be tried. For those with dose-limiting adverse effects, switching to another stimulant class or a non-stimulant is an option. For patients who are partial responders to stimulants, despite adequate adherence and dose optimization, the addition of atomoxetine or guanfacine extended release or clonidine extended release may help them achieve adequate response.